2013
DOI: 10.1007/s11010-013-1616-8
|View full text |Cite
|
Sign up to set email alerts
|

Three isoforms of the Atg16L1 protein contribute different autophagic properties

Abstract: The mammalian Atg16L1 protein consists of a coiled-coil domain and a tryptophan-aspartic acid (WD) repeat domain and is involved in the process of autophagy. However, the mechanisms underlying the effect of the Atg16L1 isoforms on autophagy remain to be elucidated in humans. In the present study, we successfully cloned three isoforms: Atg16L1-1, which contains the complete sequence; Atg16L1-2, which lacks all of exon 8; and Atg16L1-3, which lacks the coiled-coil domain. Subsequent experiments showed that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, Thachil and colleagues reported that neither the common ATG16L1 nor IRGM polymorphisms associated with CD, appeared to be responsible for the increased numbers of autophagosomes in Paneth cells (77). It is possible that other ATG16L1 variants exist, in the coiled-coil domain region for example, which would prevent efficient autophagosome degradation (80). Further characterization of the CD-associated ATG16L1 mutant proteins will likely explain the conflicting data.…”
Section: Autophagy Genes Involved In Intestinal Homeostasis and Suscementioning
confidence: 99%
“…However, Thachil and colleagues reported that neither the common ATG16L1 nor IRGM polymorphisms associated with CD, appeared to be responsible for the increased numbers of autophagosomes in Paneth cells (77). It is possible that other ATG16L1 variants exist, in the coiled-coil domain region for example, which would prevent efficient autophagosome degradation (80). Further characterization of the CD-associated ATG16L1 mutant proteins will likely explain the conflicting data.…”
Section: Autophagy Genes Involved In Intestinal Homeostasis and Suscementioning
confidence: 99%
“…5A) (27). In addition, miR-124 caused robust suppression of the selective autophagy adaptor protein p62.…”
Section: Resultsmentioning
confidence: 99%
“…Human ATG16L1 was identified by large-scale sequencing analysis of a human fetal brain cDNA library [22]. Database searching revealed that there exist at least four splice variants [22] and Jiang et al suggested the presence of seven splice variants of ATG16L1 in H. sapiens [23]. Functional analysis of three isoforms revealed different autophagic properties because of the absence of some regions of ATG16L1 which impaired their localization on autophagosomes [23].…”
Section: Atg16 Is Ubiquitous In Eukaryotes and Highly Conservedmentioning
confidence: 99%
“…Database searching revealed that there exist at least four splice variants [22] and Jiang et al suggested the presence of seven splice variants of ATG16L1 in H. sapiens [23]. Functional analysis of three isoforms revealed different autophagic properties because of the absence of some regions of ATG16L1 which impaired their localization on autophagosomes [23]. For ATG16L2 it was shown that mRNA and protein levels decreased in Multiple Sclerosis (MS) patients.…”
Section: Atg16 Is Ubiquitous In Eukaryotes and Highly Conservedmentioning
confidence: 99%